PERBEDAAN SEBELUM DAN SESUDAH PENERAPAN IFRS TERHADAP LABA BERSIH, EKUITAS DAN ABNORMAL RETURN - Ira Febrianti; Tona Aurora Lubis; Wirmie Eka Putra (Universitas Trunojoyo Madura, 2014)
This study aims to determine the differences before and after the implementation of IFRS on the financial statements of companies listed on the Stock Exchange. By looking at the difference in net income, equity and abnormal stock returns to firms in Indonesia in the IFRS convergence process using the Event Window is analyzed with nonparametric statistics: two paired sample test - Wilcoxon Signed Rank Test. The study population was all the companies listed on the Stock Exchange in 2011 and 2012. The research sample was determined using purposive and judgment sampling, obtained 78 sample firms. The results showed that there were significant differences on net income, equity and firm abnormal stock returns after implementation of IFRS.